THE USE OF PERSONAL VOCABULARY NOTES TO IMPROVE STUDENTS’ VOCABULARY MASTERY OF SMP NEGERI 3 TOTIKUM BANGGAI KEPULAUAN - Sahmawati; Rita, Ferry; Anggreni, Afrillia (e-Journal of ELTS (English Language Teaching Society), 2024)
The objective of this research is to find out whether students’ vocabulary mastery is Improve or not through personal vocabulary notes technique. This research is Pre-Experimental method. Data collection Techniques are Pre-test and Post-test. The results of this research showed that there was improvement of students' vocabulary mastery from the difference between the pre-test and post-test is 31.1, The results of the research found that students’ vocabulary this can be seen from the height of the t-conted 88.8 than t-table 1.729. Based on the result, the researcher hopes that the personal vocabulary notes technique can used improve students’ vocabulary mastery of SMP Negeri 3 Totikum